Daphne thanguensis sp. nov. (Thymelaeaceae) from Sikkim Himalaya. (3rd July 2018) - Ghosh, Jayanta; Midday, Mrinmoy; Dey, Sentu K.; Maity, D.
Abstract : Daphne thanguensis sp. nov. from north Sikkim of eastern Himalaya is described and illustrated. It is a narrow endemic related to D. tangutica Maxim. Daphne thanguensis grows in open alpine pastures and differs from D. tangutica by having leaves with revolute margin and a tuft of hairs at apex, ebracteate inflorescence and flowers, calyx lobes with a tuft of hairs at apex and annular, slightly undulate hypogynal disk. The new taxon is also close to D. retusa Hemsl. But can easily be differentiated by its sessile inflorescence, ebracteate flowers and tuft of hairs at leaf apices and calyx lobe apices. A conservation status of the new species in accordance with the IUCN red list categories and criteria is provided and discussed.